Mathematical modeling of the poly(lactic acid) ring-opening polymerization kinetics - Mehta R.; Kumar V.; Upadhyay S.N. (My University, 2025)
The modeling of ring-opening polymerization of (D,L)-lactide to poly(lactic acid) (PLA) has been performed. Except some reported data on the apparent rate constant, there is lack of data in the literature on the rate constants for initiation, propagation and termination steps of PLA polymerization. Using a simple numerical technique, the individual rate constants are evaluated theoretically and the results are compared with the available experimental data for ring-opening polymerization of PLA. The proposed method works well without requiring a polymer chain length independent rate constant. It is also shown that presence of even small amount of impurity (e.g., water) in the reaction kettle can greatly limit the polymer molecular weight.